الشعور بالمواطنة وعلاقته بالتعلق المكاني لدى سكان العشوائيات - جوني، أحمد عبدالكاظم; رضا، هناء عبدالامير محمد (جامعة القادسية - كلية الآداب, 2021)
يهدف البحث التعرف على العلاقة الارتباطية بين الشعور بالمواطنة والتعلق المكاني لدى سكان العشوائيات في مركز مدينة الديوانية، ولغرض قياس هذا الهدف، تم بناء مقياس لقياس الشعور بالمواطنة تألف بصورته النهائية من (٢٥) فقرة، وبناء مقياس آخر لقياس التعلق المكاني تألف بصورته النهائية من (٢٤) فقرة بعد التحقق من صدقهما وثباتهما وتحليل فقراتهما إحصائيا على عينة البحث البالغة (٥٠٤) مواطن ومواطنة من سكان العشوائيات، تم اختيارهم بالطريقة الطبقية العشوائية وبالأسلوب المتساوي وبعد استكمال إجراءات مقياسي البحث استخرجت النتائج عن طريق تحليل إجابات المواطنين بالاستعانة بالحقيبة الإحصائية للعلوم الاجتماعية (SPSS) عن طريق الحاسبة الإلكترونية وباستعمال مجموعة من الوسائل الإحصائية منها: (الاختبار التائي لعينتين مستقلتين، والاختبار التائي لعينة واحدة، ومعامل ارتباط بيرسون). وتوصلت نتائج البحث إلى إن سكان العشوائيات لديهم شعور عال بالمواطنة، وليس هناك فرق دال إحصائيا بالشعور بالمواطنة لدى سكان العشوائيات وفق متغير النوع (الذكور، والإناث)، وهناك فرق دال إحصائيا وفق متغير العمر ولصالح الأعمار الأكبر، كما إن سكان العشوائيات لديهم تعلق عال بالمكان، وليس هناك فرق دال إحصائيا بالتعلق المكاني لدى سكان العشوائيات وفق متغير النوع (الذكور، والإناث)، وهناك فرق دال إحصائيا وفق متغير العمر ولصالح الأعمار الأكبر، كما لا توجد علاقة ارتباطية بين الشعور بالمواطنة والتعلق المكاني لدى سكان العشوائيات، وبناء على النتائج التي خرج بها البحث وضع الباحثان مجموعة من التوصيات والمقترحات. The research aims to identify the correlation between the sense of citizenship and the place attachment of the slum dwellers in the center of Al-Diwaniyah city, and to achieve this goal, the research sample of (504) male and female citizens of the slum dwellers was selected, by the random stratified method and by the equal method, and for the purpose of measuring this goal, the Building a scale to measure the feeling of citizenship in its final form consisted of (25) items, and building another scale to measure place attachment in its final form consisted of (24) items after verifying their validity and stability and analyzing their paragraphs statistically and completing the procedures of the two search scales. The results were extracted by analyzing the citizens’ answers using the bag Statistical for Social Sciences (SPSS) through the computer and using a number of statistical methods, including: (T-test for two independent samples, T-test for one sample, and Pearson correlation coefficient). Citizenship among slum dwellers according to the gender variable (males and females), and there is a statistically significant difference according to the age variable and in favor of the age The largest, and the slum dwellers have a high attachment to the place, and there is no statistically significant difference in the spatial attachment among the slum dwellers according to the gender variable (males and females), and there is a statistically significant difference according to the age variable and in favor of the older ages, and there is no correlation between the feeling Citizenship and place attachment to slum dwellers, and based on the results of the research, the researchers developed a set of recommendations and suggestions.
Keywords: الطبقة العشوائية -- التقويم النفسي -- الشعور بالأمن -- العراق